Trends in Studies on Transesophageal Echocardiography in Emergency Medicine: A Scoping Review - Bor-Yuan Tseng; Chih-Jui Yang; Jen-Tang Sun; Yiju Teresa Liu; Kabir Yadav; Yu-Lin Hsieh; Sheng-En Chu; Chen-Wei Lee; Yi-Kung Lee; Tou-Yuan Tsai (Western Journal of Emergency Medicine)
Background: Transesophageal echocardiography (TEE) has been introduced in resuscitative scenarios in recent decades, with a growing number of emergency physicians learning, performing, and studying resuscitative TEE. Objective: Our goal was to characterize publishing trends regarding TEE use in emergency medicine (EM) and to investigate the increasing interest in potential applications of TEE in emergency departments (ED). Methods: We retrieved published research associated with the use of TEE in EM from the Web of Science database from inception to December 31, 2023. We analyzed trends based on the number of articles published annually. To systematically map trends related to TEE in emergency medicine (EM), we extracted data on the number of unique EM TEE practitioners, institutions performing EM TEE, study topics, and other characteristics from research articles and case reports. To better reflect research trends, we exclusively conducted subgroup analysis on the research articles. We used linear regression analysis to analyze trends and conducted checkpoints on the timelines. Results: Of the 964 titles and abstracts screened, we included 99 eligible published articles after careful review. Articles related to EM TEE increased from one article in 1991 to 20 articles in 2023, and the rate of publication has increased rapidly since 2018 (+12.4 publications per year, 95% confidence interval [CI] 9.8–15.0, P<0.001). The number of EM TEE practitioners and EM TEE-performing institutions underwent a rapid expansion with an inflection point between 2018–2020, with a rate of +91.7 practitioners per year and +36.5 institutions per year. Subgroup analysis revealed a similar trend in the published research articles. The most common indications for EM TEE were cardiac arrest (72.7%), shock (13.1%), and procedural guidance (11.1%). The United States published the majority of EM TEE-related articles (51.5%). Conclusion: The present study highlights that TEE-related articles in EM continue to accelerate. Among the indications for TEE, cardiac arrest remains the most frequently discussed. This scoping review provides insights into the expanding interest and applications of TEE in the field of EM.